PENGARUH MAGANG MAHASISWA DAN PENGALAMAN BERORGANISASI SERTA PRESTASI AKADEMIK TERHADAP EMPLOYABILITY (PADA MAHASISWA MAGANG FEB UNIVERSITAS RIAU) - Awaluddin Fi Firdaus; Hendriani Susi; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The world of work will experience changes made by both employers and employees themselves, Various studies highlight concerns expressed by government and industry about the ability of higher education to develop workready graduates. This study aims to examine the effect of student internships and organizational experience and academic achievement on employability. This study was conducted using primary data collected from respondents through questionnaires, while the respondents consisted of 60 students of the Management Department, Riau University who met the criteria. Then tested the hypothesis using multiple linear regression to see the effect of the independent variable on the dependent variable. In this study, the three variables have a significant effect on employability, student internships have the most dominant influence on employability, followed by academic achievement and organizational experience. The author hopes that this research can be a reference to improve students' skills to prepare for the future.Keywords: Employability, Student Internship, Organizational Experience, Academic Achievement